The Resilience of Literacy Culture in Salafi Jihadis Pesantren; Study on Traditional Islamic Boarding School in Indonesia - Abdul Malik (Journal on Education, 2023)
The existence of Salaf pesantren which is suspected to be affiliated with jihadists lately has strengthened the presence of a new traditional pesantren typology namely Salafi-jihadis. Typology pesantren are considered vulnerable to radicalism and terrorism. This article reveals the resilience of the Salafi jihadi pesantren literacy culture which is allegedly affiliated with radical jihadist groups. This was done to determine the extent of the existence of salaf-jihadis pesantren literacy. The majority of people questioned the relevance of pesantren to the spread of radicalism and terrorism issues. The data of this study were collected through observation and in-depth interviews with former convicted terrorists (suspected theorists) as well as managing Salafi-jihadis pesantren as well as several religious teachers at the pesantren. The findings of this study indicate that the salafi-jihadis pesantren teach jihad fiqh up to the ahkamudiammah chapter. However, according to the boarding school manager, the jihad literacy taught in the pesantren is recognized as having no connection with radicalism and terrorism. The findings of this study can have implications for the terminology of jihad to be pejorative. Although the majority of traditional Islamic boarding schools have diverse resistance to the issue of radicalism.